The Effects of Ankle Joint Position on Deep Peroneal Nerve Latencies - Mohamed Hussein El-Gendy; Mahmoud Salah Abd El-Fattah; Mohamed Magdy El Meligie; Efrem Kentiba; Yasser Ramzy Lasheen (Journal of Modern Rehabilitation)
Introduction: Joint positioning can impact nerve function. Few studies have explored the effects of ankle positions on deep peroneal nerve conduction. This cross-sectional study investigated the influence of different ankle joint positions on the deep peroneal nerve’s distal motor and sensory onset latencies. Materials and Methods: A total of 31 healthy adults (23.4±3.9 years old) underwent a deep peroneal nerve conduction study. Distal motor and sensory onset latencies were measured at neutral (0°), dorsiflexion (20°) and plantar flexion (40°) ankle positions. Results: Changing ankle position significantly affected distal motor (P=0.001) and sensory onset latencies (P=0.001). Latencies were shortest in dorsiflexion (motor: 3.8±0.46; sensory: 2.4±0.2 ms), followed by neutral (motor: 4.2±0.5; sensory: 2.6±0.3 ms) and most prolonged in plantar flexion (motor: 5±0.6; sensory: 3.3±0.2 ms). Conclusion: Ankle position impacts deep peroneal nerve conduction. Dorsiflexion and neutral positions reduced distal motor and sensory latencies compared to plantar flexion. These findings provide preliminary evidence that may help optimize ankle positioning in electrodiagnostic testing. Further blinded research with larger, more diverse samples is warranted.